From value-based pricing to fair pricing: the role of HTA for UHC. (30th September 2020) - Garner, S
Abstract: The UHC key concepts and relevant UN resolutions recommending transparency, including in relation to HTA and pricing. The role of innovation and intellectual property frameworks will be discussed, including financing and co-ordination of R&D for health technologies. Examples on the importance information exchange can play to improve negotiations will also be discussed, along with key considerations, commonalities and differences for for developed and developing countries.